2020
DOI: 10.1101/2020.05.04.077057
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Malignant Schwann cell precursors mediate intratumoral plasticity in human neuroblastoma

Abstract: Neuroblastoma is a heterogeneous embryonal malignancy and the most deadly tumor of childhood, although a minor subset may show spontaneous differentiation. It arises from the multipotent neural crest lineage during development. Some of this multipotency is retained in neuroblastoma, which can give rise to both adrenergic and mesenchymal tumor cells. The mechanisms enabling such dual fates are unknown, but likely help neuroblastoma to evade existing therapies. To understand neuroblastoma plasticity, we analyzed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
35
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
2

Relationship

3
3

Authors

Journals

citations
Cited by 15 publications
(40 citation statements)
references
References 45 publications
5
35
0
Order By: Relevance
“…6c right). Neuroblastomas appeared highly heterogeneous in their composition, and included malignant cells of both adrenergic and mesenchymal lineages, as reported earlier 33 , 35 , 36 . We found that the embryonic abdominal mesenchymal populations aligned with the mesenchymal cells found in tumor samples, the SCP population aligned with Schwann component from the tumor samples, and the majority of the adrenergic tumor cells showed clear similarity to embryonic sympathoblasts with a fraction of tumor cells co-aligning with chromaffin cells ( Fig.…”
Section: Resultssupporting
confidence: 72%
See 1 more Smart Citation
“…6c right). Neuroblastomas appeared highly heterogeneous in their composition, and included malignant cells of both adrenergic and mesenchymal lineages, as reported earlier 33 , 35 , 36 . We found that the embryonic abdominal mesenchymal populations aligned with the mesenchymal cells found in tumor samples, the SCP population aligned with Schwann component from the tumor samples, and the majority of the adrenergic tumor cells showed clear similarity to embryonic sympathoblasts with a fraction of tumor cells co-aligning with chromaffin cells ( Fig.…”
Section: Resultssupporting
confidence: 72%
“…For this, we carried out joint analysis of our data with scRNA-seq of neuroblastoma biopsies from two different patients explicitly described by Olsen et al . 33 ( Fig. 6a and Fig.…”
Section: Resultsmentioning
confidence: 98%
“…It is currently too early to conclude whether, when and where MES-type neuroblastoma cells exist in primary tumors in vivo 10,11,[15][16][17][18][19][20][21] . Analysis of endogenous RA signaling in MES cells may indicate whether these cells are dependent on RA signaling in vivo.…”
Section: Discussionmentioning
confidence: 99%
“…However, a recent single cell RNAseq analysis identified MES-like primary neuroblastoma that contained tumor cells with features of several developmental cell types from the adrenergic lineage 17,18 . Also several pre-print reports suggest the existence of immature tumor cells in neuroblastoma tumors [19][20][21] .…”
Section: Introductionmentioning
confidence: 99%
“…This suggests different origins for NBs that develop within the sympathetic chain and adrenal medulla, further supported by differences in dissemination and migratory behaviour, illustrated by the migratory behaviour of NB cells transplanted onto the avian embryo NC, which migrate to form primary tumours in sympathetic ganglia, then exhibit secondary migration along nerves and blood vessels, reminiscent of Schwann progenitor migratory behaviour[ 9 , 78 , 79 , 81 ]. Malignant Sox10 expressing Schwann cell progenitor subpopulations with stem cell-like features have also been reported in human NBs, connecting adrenergic and mesenchymal compartments through transitions, reminiscent of Schwann cell progenitors[ 82 ], and may or may not be involved in the formation of the Schwannian stroma that characterises favourable NBs and benign ganglioneuromas[ 83 , 84 ]. Therefore, NBs originate from either NCSCs, SA or Schwann cell progenitors or from NC cells converted into CNS SCs by aberrant N-Myc expression with full transformation within target tissues (Figure 3 ).…”
Section: Neuroblastomamentioning
confidence: 99%